Diglycidyl Ether of Bisphenol A (DGEBA) Based Epoxy Sizing Agent Induces Surface Polarity in Carbon Fibers† - Indra Neel Pulidindi (International Journal of Crystalline Materials, 2024)
Determination of the chemical structure and composition of the sizing agent is a challenge as its concentration is low, varying in the range from ~0.5 wt.% (for polyacrylonitrile, PAN, based carbon fibers) to ~1 wt.% (for pitch-based carbon fibers). Moreover, such a piece of knowledge is vital for designing compatible polymer matrices to prepare CFRPs for diverse applications. As a result, the sizing layer that is coated on the carbon fiber (CF) surface in the commercial sizing process was isolated from the commercial carbon fibers (NX90, NX100, M55J, T700SC, CCF800H, T800HB) and examined using FT-IR spectroscopy. The results revealed that the epoxy resin, the diglycidyl ether of bisphenol A (DGEBA), is the sizing composition's major constituent. Epoxy sizing with sizing composition, comprising of DGEBA derivative, polysiloxanes, and esters, is surmised to improve the compatibility of CFs with resin matrices. In all the CFs examined, the sizing composition comprised of DGEBA derivative with polyorganosiloxanes. Characteristic bands at 829, 948, 1509, and 1607 cm⁻¹ attributable to C–O–C stretching vibration of oxirane, C–O stretching of oxirane, C–C stretching vibration of benzene, and C=C stretching vibration of benzene signify that DGEBA molecule is used in the sizing composition of all the commercial carbon fibers examined. Moreover, the four consecutive bands in the range of 2870–3065 cm⁻¹ were observed. These bands were characteristic of CH stretching vibrations of methylene groups (~2870 and 2924 cm⁻¹), aromatic CH stretching (~2963 cm⁻¹), and CH stretching of terminal epoxy (~3065 cm⁻¹) groups of DGEBA derivative in the sizing composition. Further insights into the molecular-level composition and interaction of the sizing compound with the carbon fiber surface as well as the resin matrix are necessary for developing carbon fiber reinforced composites with desired surface and mechanical properties and applications.
Keywords: CFRPs; Carbon fibers; Composites; FT - IR spectroscopy; PAN; Resins; characterization; epoxy sizing; interface; pitch; polyacrylonitrile; surface functionalization